1995
DOI: 10.1002/eji.1830250430
|View full text |Cite
|
Sign up to set email alerts
|

Epitope specificity, cytokine production profile and diabetogenic activity of insulin‐specific T cell clones isolated from NOD mice

Abstract: T cells are known to play an important role in beta cell destruction in the nonobese diabetic (NOD) mouse model of Type I diabetes and islet-specific T cell clones have been demonstrated to be capable of adoptive transfer of diabetes. One important issue involves the identity of beta cell antigens that are recognized by nominally islet cell-specific T cell clones. We have previously reported that insulin-specific T cells are a predominant component of islet-specific T cells isolated from islet infiltrates of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
291
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(307 citation statements)
references
References 52 publications
(24 reference statements)
7
291
0
Order By: Relevance
“…Animals were immunised subcutaneously with 100 µg insulin B9-23 peptide (amino acids 9-23 of the B chain; SHLVEALYLVCGERG) [17,18] in complete Freund's adjuvant, together with 140 µg of a helper peptide consisting of amino acids 128-140 of hepatitis B virus core antigen (TPPAYRPPNAPIL), at the base of the tail. After 12-14 days, an i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Animals were immunised subcutaneously with 100 µg insulin B9-23 peptide (amino acids 9-23 of the B chain; SHLVEALYLVCGERG) [17,18] in complete Freund's adjuvant, together with 140 µg of a helper peptide consisting of amino acids 128-140 of hepatitis B virus core antigen (TPPAYRPPNAPIL), at the base of the tail. After 12-14 days, an i.p.…”
Section: Methodsmentioning
confidence: 99%
“…It is clear that in NOD mice the disease process is Th-1 driven. However, although Th-2 cells dominate non-destructive periinsulitis in these mice, IL-4 producing Th-cell clones are capable of adoptive transfer of insulitis or even diabetes to non-diabetic immunoincompetent NODscid recipients [89,90], and incapable to prevent disease [89].…”
Section: Cytokinesmentioning
confidence: 99%
“…Insulin, and particularly the 9-23 peptide of the insulin beta chain, is a primary target of T cell reactivity in both the human disease and the NOD mouse [38,39] (in this issue, contribution by Eisenbarth). Initial binding studies of the B:(9-23) peptide to soluble I-A g7 in detergent free conditions revealed poor binding and fast dissociation rates [10,13,14,40].…”
Section: Weak Mhc Binding Peptides and Autoreactivity: The Case Of Thmentioning
confidence: 99%